Teacher’s Role in Developing Student Discipline Character during The New Normal Era at SDIT Al-Khairiyah Cilegon - Dewi, Ajeng Mustika; Hakim, Zerri Rahman; Jamaludin, Ujang (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Education is not only about academics but also about the development of character values, including in education. Given how essential character education is, efforts to develop character values continue to be carried out, where one of the characteristics that need to be fostered is the character of discipline even in the new normal era. This research was conducted to find out: 1) efforts to develop the discipline character of students, 2) the role of the teacher in implementing the discipline character of students, and 3) the discipline character of grade IV/B students in the new normal era at SDIT Al-Khairiyah Cilegon. The method employed in this research was qualitative, following the data and facts found, and then the data used in this study were obtained through non-participatory observations, which the researchers put into field notes, documents, and interviews with several sources. The results of this study highlighted that 1) teachers were firm in enforcing rules, applying exemplary habits, and setting good examples for students. 2) The grade IV/B homeroom teacher continuously attempted to set an example of discipline, one of which was by arriving on time. Then, the school provided support, such as improving school facilities and infrastructure and working with the surrounding health centers to provide socialization and vaccination to students to prevent the spread of the COVID-19 virus. 3) The disciplinary character of students has developed with the resumption of habituation activities in the new normal era, so the implication going forward is that students become more obedient to the applicable rules in everyday life